Alexithymia and Problematic Mobile Phone Use: A Moderated Mediation Model - Hao, Zejun; Jin, Liangyi (Frontiers in Psychology, 2020)
Alexithymia has been studied with its impact on problematic mobile phone use. However, none of these studies has tested the roles of mindfulness facets in this relationship. Methods To address this issue, a total of 901 Chinese undergraduate students participated in this study and were tested with questionnaires for measuring their levels of alexithymia, problematic mobile phone use and mindfulness facets. Results showed that alexithymia predicted problematic mobile phone use both directly and indirectly via mindfulness facet of acting with awareness. Namely, the facet of acting with awareness partially mediated this relationship. Further, the facet of observing moderated the path between alexithymia and the facet of acting with awareness, with the impact of alexithymia on the facet of acting with awareness becoming stronger under the condition of the high level of the facet of observing. The current study advanced our understanding on the mechanism underlying the connection between alexithymia and problematic mobile phone use.